Gd3+ electron spin resonance spectroscopy on LaO1−xFx FeAs superconductors - Alfonsov, Alexey; Klingeler, Rüdiger (Journal of experimental and theoretical physics, 2012)
We report an electron spin resonance (ESR) spectroscopy study on polycrystalline samples of the LaO1 − x F x FeAs (x = 0 and 0.1) compound with small levels of Gd doping (2% and 5%). The Gd ESR signal is found to be sensitive to the magnetic phase transition from the paramagnetic to the spin density wave (SDW) state occurring in the parent LaO1 − x F x FeAs compounds at T SDW ∼ 130 K. Interestingly, the analysis of the low-temperature ESR spectra of the c-axis oriented Gd1 − y La y OFeAs samples gives evidence for the magnetically nonequivalent Gd sites and also for sites having a different local charge environment. The analysis of the temperature dependence of the ESR linewidths gives evidence for a coupling of the localized 4f electrons of Gd to the conduction electrons in the FeAs layers. The ESR data reveal that the fluorine substitution, which provides electron doping, suppresses the SDW order and enhances the density of states in the electronic bands stemming from the xz and yz orbital states of Fe to which the 4f electrons are most strongly coupled.